Polymorphism of Syndiotactic Polystyrene Crystals from Multiscale Simulations. Issue 7 (16th May 2018) - Liu, Chan; Kremer, Kurt; Bereau, Tristan
Abstract: Syndiotactic polystyrene (sPS) exhibits complex polymorphic behavior upon crystallization. Computational modeling of polymer crystallization has remained a challenging task because the relevant processes are slow on the molecular time scale. A detailed characterization of sPS‐crystal polymorphism by means of coarse‐grained (CG) and atomistic (AA) modeling is reported herein. The CG model, parametrized in the melt, shows remarkable transferability properties in the crystalline phase. Not only is the transition temperature in good agreement with atomistic simulations, it stabilizes the main α and β polymorphs, observed experimentally. The propensities of polymorphs at the CG and AA levels are compared in detail, as well as finite‐size and box‐geometry effects. All in all, CG modeling stands as an efficient approach to characterize polymer‐crystal poymorphism at large scale. Abstract : Polymers exhibit complex polymorphic behavior upon crystallization . Computational modeling has remained a challenging task because the relevant processes are slow on the molecular time scale. A detailed characterization of crystal polymorphism is reported by means of coarse‐grained and atomistic modeling. The appeal of coarse‐graining to study the self‐assembly and stability of polymer‐crystal polymorphism is demonstrated.